Associations Between Sympathetic Nervous System Synchrony, Movement Synchrony, and Speech in Couple Therapy - Tourunen, Anu; Nyman-Salonen, Petra; Muotka, Joona; Penttonen, Markku; Seikkula, Jaakko; Kykyri, Virpi-Liisa (Frontiers in Psychology, 2022)
Background: Research on interpersonal synchrony has mostly focused on a single modality, and hence little is known about the connections between different types of social attunement. In this study, the relationship between sympathetic nervous system synchrony, movement synchrony, and the amount of speech were studied in couple therapy. Methods: Data comprised 12 couple therapy cases (24 clients and 10 therapists working in pairs as co-therapists). Synchrony in electrodermal activity, head and body movement, and the amount of speech and simultaneous speech during the sessions were analyzed in 12 sessions at the start of couple therapy (all 72 dyads) and 8 sessions at the end of therapy (48 dyads). Synchrony was calculated from cross-correlations using time lags and compared to segment-shuffled pseudo synchrony. The associations between the synchrony modalities and speech were analyzed using complex modeling (Mplus). Findings: Couple therapy participants’ synchrony mostly occurred in-phase (positive synchrony). Anti-phase (negative) synchrony was more common in movement than in sympathetic nervous system activity. Synchrony in sympathetic nervous system activity only correlated with movement synchrony between the client-therapist dyads (r=.66 body synchrony, r=.59 head synchrony). Movement synchrony and the amount of speech correlated negatively between spouses (r=-.62 body synchrony, r=-.47 head synchrony) and co-therapists (r=-.39 body synchrony, r=-.28 head synchrony), meaning that the more time the dyad members talked during the session, the less bodily synchrony they exhibited. Conclusion: The different roles and relationships in couple therapy were associated with the extent to which synchrony modalities were linked with each other. In the relationship between clients and therapists, synchrony in arousal levels and movement “walked hand in hand”, whereas in the other relationships (spouse or colleague) they were not linked. Generally, more talk time by the therapy participants was associated with anti-phase movement synchrony. If, as suggested, emotions prepare us for motor action, an important finding of this study is that sympathetic nervous system activity can also synchronize with that of others independently of motor action.